The future starts in the past: embedding learning for sustainability through culture and community in Scotland - White, Rehema M.; Kockel, Ullrich; King, Betsy; Leask, Kirsten; Higgins, Peter; Samuel, Andrew (Frontiers in Sustainability, 2023)
Introduction If sustainability is about imagining and pursuing desired futures, our past history, heritage, and culture will influence the kind of futures we seek and our chosen routes towards them. In Scotland, there is a strong connection between culture, land, and identity; a sense of community; and a perception of work ethic that derive from our biogeography and socio-political journey. Concepts and practises of education have been influenced by the ideas of key thinkers such as the Scot Sir Patrick Geddes, who introduced approaches to education and community through concepts such as “heart, hand, and head”, “think global, act local,” and “place, work, and folk”. This background influenced us in establishing Scotland's United Nations University-recognised Regional Centre of Expertise (RCE) in Education for Sustainable Development (ESD), known locally as “Learning for Sustainability Scotland”. Its initial development ten years ago and subsequent evolution have been built on engaging collaboratively across Scotland and linking formal, non-formal, and informal modes of learning for sustainability. In this paper, we explore how culture and context have influenced the emergence, governance, and activities of RCE Scotland over the past decade. Methods We developed an analytical framework of possible cultural and contextual influences on Scottish education. We used a Delphi approach to develop a novel and locally relevant definition of ESD when the RCE was established. Results Analysis of purposively selected RCE Scotland activities against our cultural framework illustrated how they had been influenced by culture or context. We propose that democratic intellect, local and global, and nature-culture connections have informed our initiative. Discussion We conclude that connection to people, place, and nature influences engagement and action on sustainability, and we suggest that additional sustainability competencies should include physical, emotional, and spiritual aspects of nature connection.